2008
DOI: 10.1055/s-2008-1081293
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilisFZB24® Affects Flower Quantity and Quality of Saffron (Crocus sativus)

Abstract: The effect of Bacillus subtilis FZB24® on saffron (Crocus sativus L.) was studied using saffron corms from Spain and the powdered form of B. subtilis FZB24®. Corms were soaked in water or in B. subtilis FZB24 spore solution for 15min before sowing. Some corms were further soil drenched with the spore solution 6, 10 or 14 weeks after sowing. Growth and saffron stigma chemical composition were measured. Compared to untreated controls, application of B. subtilis FZB24 significantly increased leaf length, flowers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 13 publications
2
12
0
1
Order By: Relevance
“…B. subtilis has already been reported to possess saffron plant growth promotion potential. According to Eldin et al ( 2008 ) saffron corms treated with B. subtilis suspension result in speeding of corm growth, increased stigma biomass as well as increased carotenoid pigment production. Liu et al ( 2009 ) reported that the ginseng seedlings exhibit increased biocontrol, growth promotion and stress resistance properties when sown in soil inoculated with B. subtilis.…”
Section: Resultsmentioning
confidence: 99%
“…B. subtilis has already been reported to possess saffron plant growth promotion potential. According to Eldin et al ( 2008 ) saffron corms treated with B. subtilis suspension result in speeding of corm growth, increased stigma biomass as well as increased carotenoid pigment production. Liu et al ( 2009 ) reported that the ginseng seedlings exhibit increased biocontrol, growth promotion and stress resistance properties when sown in soil inoculated with B. subtilis.…”
Section: Resultsmentioning
confidence: 99%
“…Saffron (C. sativus L.) is one of the most valuable and expensive spices; it has high medicinal value and is used in the treatment of many diseases. The production of saffron is a very low worldwide because of its growth characteristics and high demand for labor (Sharaf-Eldin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the recent past, it has been produced by breeders, which provides a better platform for maintaining its genetic balance. The quality of saffron mainly depends upon stigma processing and species origin (Sharaf-Eldin et al, 2008). Caiola, Somma, and Lauretti (2000) reported that the phenological evaluation of C. sativus flowers obtained from corms from various regions of the world showed some variation in the color of the flowers as well as their fragrance and tepal lobes, but not in the pollen size (Caiola et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Las PGPR inducen el crecimiento y el rendimiento de los cultivos a través de una variedad de mecanismos de acción directos e indirectos (GOUDA et al, 2018) documentados en otros cultivos (e.g., azafrán, trigo, maíz, algodón, banana), allí se concluyó que Bacillus spp. incrementó la cantidad total de flores, número de frutos formados e incrementó el peso medio del fruto (ESITKEN et al, 2006;SHARAF-ELDIN et al, 2008;HUSSEINI;BOCHOW;JUNGE, 2012).…”
Section: Introductionunclassified